Purification of Carbon-Based Magnetic Nanoparticles (CMNs) Produced by Submerged Arc Discharge in Liquid Ethanol/Ethylenediamine - Oktaviana Dyah Mayasari; Dielsa Eka Kuswari; Witri Wahyu Lestari; Teguh Endah Saraswati (Molekul, 2021)
Surface modification of covalently amine-attached carbon-based magnetic nanoparticles (CMNs) can be produced quite simply in submerged arc discharge using the amine-containing liquid medium ethylenediamine (ED), resulting in CMNs-ED. However, after the arc discharge processing, the resulting nanoparticles possibly contain physically absorbed amine-containing molecules from a liquid medium on the particle surface. To remove the non-covalently bound molecules, a purification process is required. In this study, the purification was conducted using polar and non-polar solvents following the synthesis process. The surface property was initially characterized by a dispersion test in water, showing that CMNs-ED purified by water have better dispersion than CMNs produced in ethanol alone, CMNs-ED before purification, and CMNs-ED after purification by immersion in toluene. Before and after purification, the diffraction pattern showed definitive peaks corresponded to the crystal planes of C(002), Fe3C(220), and Fe3O4(311) at 26.51°, 44.65°, and 35.42°, respectively. The amine functional group on the nanoparticles before purification thought to come from decomposed ethylenediamine assigned by the vibration peaks appeared at a wavenumbers ~3400 cm-1 and 1020-1220 cm-1, which corresponds to N-H and C-N, respectively. After purification, the vibration peaks of amine groups were still observable, indicating that the amine groups were still covalently attached to the nanoparticles. Magnetic analysis showed that CMNs before and after purification have superparamagnetic properties, with the magnetic saturation value around 10-17 emu/g. The electron microscope images show that the CMNs-ED before purification have a spherical form with a diameter larger than CMNs-ED after purification.